Hediste diversicolor sensu Hartmann-Schroder 1996 - Salazar-Vallejo, Sergio I.; León-González, Jesús Angel De; Conde-Vela, Víctor M. (Zenodo, 2021)
Hediste diversicolor (Müller, 1776) Nereis diversicolor Müller, 1776: 217 Nereis diversicolor – Örsted 1843: 23, figs 66, 68, 73. — Müller 1800: 104–118, pl. 6 figs 1–6. — McIntosh 1910: 312–324. — Heinen 1911: 46–49. — Fauvel 1923: 344, fig. 133a–f. — Chambers & Garwood 1992: 28–31, fig. 41. Hediste diversicolor – Malmgren 1867: 165–166, pl. 28 fig. 28. — Bakken 2004: 34–35, fig. 1 1. Nereis ( Hediste ) diversicolor – von Marenzeller 1874: 466–469, pl. 7 fig. 3. — Hartmann-Schröder 1996: 201–204, fig. 88. Remarks The taxonomic history of Hediste diversicolor is rather complex and has not been fully resolved. The original description was “body subdepressed, parapodia tapered with chaetae” (Müller 1776: 217), and no Greenlandic name or type locality was indicated; after invoking the ICZN, the Commission has moved to conclude that “the type locality has not been clarified” (Oug et al . 2014: 220). However, recommendation 76A1.3 is to take into account “the original description of the taxon”. The second line for the original description includes two references: “Würm. 104, t. 6, Str. S. 1, p. 198, 2?” The first is a previous paper by the author (Müller 1771), whereas the latter is a paper: “Physik og oeconomisk Beskrievelse over fogderiet Söndmör” by Hans Ström (published in Soröe [Sorø, Denmark] in 1762). We could not find the latter, but we found two editions of the former which contain an extended description (Müller 1771: 102–111, pl. 6 figs 1–6) and indications that the specimens were collected in Copenhagen. This information complies with the recommendation, and consequently the type locality should be Copenhagen, Denmark. It was reiterated in the second edition (Müller 1880: 110). Furthermore, specimens identified as H. diversicolor from the Baltic Sea include at least two different species, and this has complicated solving what we should regard as this biological species (Virgilio et al . 2009; Tosuji et al . 2019). Örsted (1843: 23) provided a description of Nereis diversicolor and included illustrations of the anterior end, one jaw and one parapodium (pl. 4 figs 66, 68, 73). From the description, he emphasized that the tentacular cirri could reach segments 5–6, that dorsal cirri were short, parapodial ligules tapered and the notopodia had three ligules. He also indicated that this was a very common species living in sediments along Danish coasts, and in the synonymy he listed the species that Rathke (1837a) had recorded as Lycoris pulsatoria? Örsted relied on the original description by Rathke (1837a) and on the additional detailed account of its anatomy published separately (Rathke 1837b). Because the typical N. diversicolor and the recorded specimens of L. pulsatoria? have three notopodial ligules, he regarded them as synonymous. On the other hand, Malmgren (1867: 48–49) used the number of notopodial ligules in his key to genera, and for species having three ligules he proposed Hediste , with N. diversicolor as its only species and listing N. sarsi Rathke, 1843, described from Molde, Norway, and N. depressa Frey & Leuckart, 1847, described from Helgoland, as synonyms. Malmgren did not use the diagnostic anchylosed neurofalcigers in his diagnosis, nor in the species description, and did not illustrate them. Ehlers (1868: 554) added N. brevimanus Johnston, 1840, described from Ireland, to the list of synonyms, provided a complete description and indicated that Hediste diversicolor could also be found in fresh-water environments. : Published as part of Salazar-Vallejo, Sergio I., León-González, Jesús Angel De & Conde-Vela, Víctor M., 2021, Revision of the species confused with " Nereis falsa " de Quatrefages, 1866 (Annelida, Nereididae), pp. 1-70 in European Journal of Taxonomy 779 on pages 8-9, DOI: 10.5852/ejt.2021.779.1579, http://zenodo.org/record/5724311 : {"references": ["Muller O. F. 1776. Zoologiae Danicae Prodromus, seu Animalium Daniae et Norvegiae Indigenarum Characters, Nomina, et Synonyma Imprimis Popularium. Hallageriis, Havniae [Copenhagen]. https: // doi. org / 10.5962 / bhl. title. 13268", "Orsted A. S. 1843. Annulatorum Danicorum Conspectus, Fasc. 1. Maricolae. Wahlianae, Hafniae [Copenhagen]. Available from https: // www. biodiversitylibrary. org / item / 44441 page / 3 / mode / 1 up [accessed 16 Sep. 2021].", "Muller O. F. 1800. Naturgeschichte einiger Wurm-Arten, des sussen und salzigen Wassers. Johann Heinrich Schubothe, Copenhagen. https: // doi. org / 10.5962 / bhl. title. 14413", "McIntosh W. C. 1910. A Monograph of the British Annelids, volume 2, part 2. Polychaeta: Syllidae to Ariciidae: 233 - 444. Ray Society, London. Available from https: // www. biodiversitylibrary. org / item / 118633 page / 13 / mode / 1 up [accessed 16 Sep. 2021].", "Heinen A. 1911. Die Nephtydeen und Lycorideen der Nord- und Ostsee einschliesslich der verbindenden Meeresteile. Wissenschaftliche Meeresuntersuchungen, New Series 13: 1 - 85. Available from https: // www. biodiversitylibrary. org / item / 53069 page / 11 / mode / 1 up [accessed 16 Sep. 2021].", "Fauvel P. 1923. Polychetes errantes. Faune de France 5: 1 - 488.", "Chambers S. & Garwood P. 1992. Polychaetes from Scottish Waters: A Guide to Identification 3. Family Nereidae. National Museums of Scotland, Edinburgh.", "Malmgren A. J. 1867. Annulata Polychaeta Spetsbergiae, Groenlandiae, Islandiae et Scandinaviae hactenus cognita. Frenckelliana, Helsingsforsiae [Helsinki]. https: // doi. org / 10.5962 / bhl. title. 13358", "Bakken T. 2004. A Revision of Nereidinae (Polychaeta, Nereididae). PhD thesis. Norwegian University of Science and Technology, Trondheim. Available from https: // ntnuopen. ntnu. no / ntnu-xmlui / handle / 11250 / 272013 [accessed 16 Sep. 2021].", "von Marenzeller E. 1874. Zur Kenntnis der adriatischen Anneliden. Sitzungsberichte der kaiserliche Akademie der Wissenschaften, Mathematisch-Naturwissenschaftliche Classe, Wien 69: 407 - 482. Available from https: // www. biodiversitylibrary. org / item / 35268 page / 441 [accessed 16 Sep. 2021].", "Hartmann-Schroder G. 1996. Annelida, Borstenwurmer, Polychaeta. Tierwelt Deutschlands 58: 1 - 648.", "Oug E., Bakken T. & Kongsrud J. A. 2014. Original specimens and type localities of early described polychaete species (Annelida) from Norway, with particular attention to species described by O. F. Muller and M. Sars. Memoirs of Museum Victoria 71: 217 - 236. https: // doi. org / 10.24199 / j. mmv. 2014.71.17", "Muller O. F. 1771. Von Wurmern des sussen und salzigen Wassers. Seinect und Faber, Copenhagen. Available from https: // www. biodiversitylibrary. org / item / 50349 page / 5 / mode / 1 up [accessed 16 Sep. 2021].", "Virgilio M., Fauvelot C., Constantini F., Abbiati M. & Backeljau T. 2009. Phylogeography of the common ragworm Hediste diversicolor (Polychaeta: Nereididae) reveals cryptic diversity and multiple colonization events across its distribution. Molecular Ecology 18: 1980 - 1994. https: // doi. org / 10.1111 / j. 1365 - 294 X. 2009.04170. x", "Tosuji H., Bastrop R., Gotting M., Park T., Hong J. - S., Sato M. 2019. Worldwide molecular phylogeny of common estuarine polychaetes of the genus Hediste (Annelida: Nereididae), with special referenc to interspecific common haplotypes found in southern Japan. Marine Biodiversity 49: 1385 - 1402. https: // doi. org / 10.1007 / s 12526 - 018 - 0917 - 2", "Rathke H. 1837 a. Zur Fauna der Krym. Memoires de l'Academie imperiale des Sciences de St. Petersbourg (Memoirs des Savants etrangers) 3: 290 - 454. Available from http: // www. biodiversitylibrary. org / bibliography / 11609 / summary [accessed 16 Sep. 2021].", "Rathke H. 1837 b. De Bopyro et Nereide: Commentationes Anatomico-Physiologicae Duae. Frantzen, Rigae and Dorpati [Riga and Tartu, Estonia]. https: // doi. org / 10.5962 / bhl. title. 14421", "Ehlers E. 1868. Die Borstenwurmer (Annelida Chaetopoda) nach systematischen und anatomischen Untersuchungen dargestellt 2: 269 - 748. Wilhelm Engelmann, Leipzig. Available from https: // www. biodiversitylibrary. org / page / 1985162 page / 321 / mode / 1 up [accessed 16 Sep. 2021]."]}